Structural vector autoregressions with smooth transition in variances: The interaction between US monetary policy and the stock market - Helmut Lütkepohl; Aleksei Netšunajev (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In structural vector autoregressive analysis identifying the shocks of interest via heteroskedasticity has become a standard tool. Unfortunately, the approaches currently used for modelling heteroskedasticity all have drawbacks. For instance, assuming known dates for variance changes is often unrealistic while more exible models based on GARCH or Markov switching residuals are difficult to handle from a statistical and computational point of view. Therefore we propose a modelbased on a smooth change in variance that is exible as well as relatively easy to estimate. The model is applied to a five-dimensional system of U.S. variables to explore the interaction between monetary policy and the stock market. It is found that previously used conventional identification schemes in this context are rejected by the data if heteroskedasticity is allowed for. Shocks identified via heteroskedasticity have a different economic interpretation than the shocks identified using conventional methods.
Keywords: C32; 330; structural vector autoregressions; heteroskedasticity; smooth transition VAR models; identification via heteroskedasticity